2020
DOI: 10.30659/odj.7.1.31-39
|View full text |Cite
|
Sign up to set email alerts
|

Disclosing Agent From Red Dragon Fruit Peel as Dental Plaque Indicator

Abstract: Background: Red dragon fruit peel mucoadhesive gel has the potential to dye dental plaque. The colour of a transparent dental plaque can be seen with visualize using dyes (disclosing agent). One of the natural products containing dyestuff betacyanin, namely the peel of the red dragon (Hylocereus polyrhizus). This research aimed to review the peels of red dragon betacyanin (Hylocereus polyrhizus) in the mucoadhesive gel formula as an alternative disclosing agent. Method: Research is done with the manufacture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…12,21,25,26 Synthetic disclosing the solution is known to have shortcomings in terms of safety because it has the potential to be a carcinogen if swallowed and used continuously, the color lasts a long time, and the taste is unpleasant, while super red dragon fruit juice has advantages in terms of safety because it has a sweet taste that does not cause danger or allergic reactions if swallowed. 12,18,21 Sefyana et al, 27 explained that this can occur due to differences in the attachment of colors between synthetic disclosing solution and super red dragon fruit juice on dental plaque that unites with the environment of the oral cavity where there is saliva.…”
Section: Discussionmentioning
confidence: 99%
“…12,21,25,26 Synthetic disclosing the solution is known to have shortcomings in terms of safety because it has the potential to be a carcinogen if swallowed and used continuously, the color lasts a long time, and the taste is unpleasant, while super red dragon fruit juice has advantages in terms of safety because it has a sweet taste that does not cause danger or allergic reactions if swallowed. 12,18,21 Sefyana et al, 27 explained that this can occur due to differences in the attachment of colors between synthetic disclosing solution and super red dragon fruit juice on dental plaque that unites with the environment of the oral cavity where there is saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Bahan yang digunakan untuk mendeteksi plak adalah disclosing agent. Disclosing agent berkerja dengan memberikan warna pada bakteri dalam plak sehingga terdapat perbedaan warna antara plak dan gigi (Purbaningtyas et al, 2020). Disclosing agent memiliki berbagai bentuk sediaan mulai dari larutan, tablet, gel (Febriyanti et al, 2018).…”
Section: Pendahuluanunclassified
“…The findings of this study confirm the findings of other studies, which found a correlation between calculus index and unilateral chewing behavior in high school students. [14][15][16] Of the twenty people who chewed on one side, eight had moderate OHIS, four showed good OHIS, and four showed insufficient OHIS. Biting on the side of the mouth that is not directly above the gum line is associated with an increased risk of dental calculus accumulation, and this study corroborates the findings of other studies.…”
Section: Chew On One Side Oral Hygiene P-value Mean±sdmentioning
confidence: 99%